Forming a joint dialogue among faith healers, traditional healers and formal health workers in mental health in a Kenyan setting: towards common grounds. Issue 1 (December 2016) - Musyimi, Christine; Mutiso, Victoria; Nandoya, Erick; Ndetei, David
Abstract Background Qualitative evidence on dialogue formation and collaboration is very scanty in Kenya. This study thus aimed at the formation of dialogue and establishment of collaboration among the informal (faith and traditional healers) and formal health workers (clinicians) in enhancing community–based mental health in rural Kenya. Methods Qualitative approach was used to identify barriers and solutions for dialogue formation by conducting nine Focus Group Discussions each consisting of 8–10 participants. Information on age, gender and role in health care setting as well as practitioners' (henceforth used to mean informal (faith and traditional healers) and formal health workers) perceptions on dialogue was collected to evaluate dialogue formation. Qualitative and quantitative data analysis was performed using thematic content analysis and Statistical Package Social Sciences (SPSS) software respectively. Results We identified four dominant themes such as; (i) basic understanding about mental illnesses, (ii) interaction and treatment skills of the respondents to mentally ill persons, (iii) referral gaps and mistrust among the practitioners and (iv) dialogue formation among the practitioners. Although participants were conversant with the definition of mental illness and had interacted with a mentally ill person in their routine practice, they had basic information on the causes and types of mental illness. Traditional and faith healers felt demeaned by the clinicians who disregarded their mode of treatment stereotyping them as "dirty". After various discussions, majority of practitioners showed interest in collaborating with each other and stated that they had joined the dialogue in order interact with people committed to improving the lives of patients. Conclusion Dialogue formation between the formal and the informal health workers is crucial in establishing trust and respect between both practitioners and in improving mental health care in Kenya. This approach could be scaled up among all the registered traditional and faith healers in Kenya.